Human Resource Optimization Efforts Through Digital Transformation In The Boiler Division Of PT. Daese Garmen - Nugraha, Ega; Noor, Sa'ad (Pascasarjana STIE Miftahul Huda, 2025)
Digital transformation has become a strategic necessity for the manufacturing industry in facing market dynamics and operational efficiency challenges. This study aims to analyze the implementation of digital transformation in optimizing human resources (HR) in the Boiler Division of PT Daese Garmen. Using a qualitative descriptive approach and case study method, data were collected through direct observation and semi-structured interviews. The results show that digitalization of work systems, such as computer-based steam pressure recording, QR/barcode-based attendance, and digital SOP distribution, successfully increased operational efficiency and accuracy. A job enlargement strategy was also implemented by transferring some helper tasks to foreman positions, in response to workforce reductions. Workload Analysis (WLA) revealed a gap between actual HR capacity and ideal needs, particularly for helper positions. These optimization efforts demonstrate that synergy between technology, employee training, and adaptive management is key to successful digital transformation in the context of technical work.